Are network effects really all about size? The role of structure and conduct. (30th August 2012) - Afuah, Allan
Abstract Rooted in neoclassical economics, network effects research has revolved around size, arguing that the more users a network has, the more valuable that network will be to each user. I argue that a network's structure (feasibility of transactions, centrality of members, structural holes, network ties, the number of roles each member plays) and its conduct (opportunistic behavior, reputation signaling, perceptions of trust) also have significant impacts on a network's value to users and to network providers. Network research that neglects structure and conduct and focuses only on size can lead to wrong strategies or a misleading research agenda. Copyright © 2012 John Wiley & Sons, Ltd.